2004
DOI: 10.1021/jp0361273
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire-Based Molecular Monolayer Junctions:  Synthesis, Assembly, and Electrical Characterization

Abstract: Nanowire metal-molecule-metal junctions containing dithoilated molecules of dodecane (C12), oligo-(phenylene ethynylene) (OPE), and oligo(phenylene vinylene) (OPV) were prepared by replicating the pores of sub-40 nm diameter polycarbonate track etched membranes. Bottom Au-S or Pd-S contacts were made by potential-assisted molecule assembly onto the tips of the first segment of the electrochemically deposited nanowires. Top S-Ag or S-Pd contacts were formed by depositing Ag or Pd nanoparticles, which also serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 47 publications
6
154
2
2
Order By: Relevance
“…Measurements of the conductance through oligophenylenes and carotanoids of different length also showed exponential dependence on molecule length, but with a smaller decay constant as expected [23,24]. Comparison of the conductance through alkanes to that through prototypical molecular wires with extended pi electron states (oligophenyleneethynylene, OPV and oligophenylenevinylene, OPV) showed substantially higher conductance through the conjugated molecules and a rational dependence on the HOMO-LUMO gap [23,[25][26][27]. In a series of asymmetric junctions formed with oligophenyl and acene monothiols, systematic changes in conductance with electrode Fermi level alignment were observed [28].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Measurements of the conductance through oligophenylenes and carotanoids of different length also showed exponential dependence on molecule length, but with a smaller decay constant as expected [23,24]. Comparison of the conductance through alkanes to that through prototypical molecular wires with extended pi electron states (oligophenyleneethynylene, OPV and oligophenylenevinylene, OPV) showed substantially higher conductance through the conjugated molecules and a rational dependence on the HOMO-LUMO gap [23,[25][26][27]. In a series of asymmetric junctions formed with oligophenyl and acene monothiols, systematic changes in conductance with electrode Fermi level alignment were observed [28].…”
Section: Introductionmentioning
confidence: 67%
“…Our finding that the ethynyl case has lower conductance than the vinyl case agrees with ensemble measurements for longer oligomers (three phenyls instead of two here). However, the ensemble measurements, performed for SAMs on crossed wire junctions [25] and in-wire junctions [26]), show a larger ratio between the OPV and OPE conductance (about 3x). In our case, the relatively small changes in conductance are consistent with the differences in N-N distance (assuming all three species to be approximately flat) and an exponential decay constant of 0.4 per Å.…”
Section: Short "Molecular Wires" and Conformationmentioning
confidence: 93%
“…The current consensus in the field of molecular electronics is that charge transport in SAMs of insulating organic molecules proceeds via non-resonant, through-bond tunneling. 20,23,34,42,[57][58][59][60][61][62][63][64] We 19,21-23 and others [66][67][68] have previously reported that J through SAMs of nalkanethiols is approximately log-normally distributed (albeit often with long, asymmetrical tails and significant outliers), rather than normally distributed, and have suggested that variations from junction to junction in thickness and in the number or type of defects in the SAM and electrodes would lead to a normal distribution in the effective thickness, d, of the SAM. 19,[21][22][23]66,69 Since J is exponentially dependent on a normally distributed parameter (eq.…”
Section: Introductionmentioning
confidence: 99%
“…Vertically oriented metalcatalyzed NWs, termed "nanocolonnades," are grown from the bottom layer (bottom electrode) and epitaxially connected to the top electrode--resembling the formation of "stalagmites" [94]. The obvious uniqueness to use bridging NW technique is the ability to directly connect structures using grown silicon NWs, whereas other processes have picked and placed silicon NWs to make similar connections [95]. One of the current challenges in a bridging process is deposition of the catalyst material only into the regions selected for NW growth.…”
Section: B Configurationsmentioning
confidence: 99%